Climbing to the top of Mount Everest is hard, but it's slightly easier than you might think as people weigh less as they climb to the top. Let W E be a person's weight on top of Mount Everest and W S be their weight at sea level. What is the value of 1 − W E / W S ?
Details and assumptions
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let x be your weight at sea level and r is the distance to the center of the earth
Your weight on the top of Everest will be (r / (r + height of Everest))^2 * x
Log in to reply
yes you are also right. In this way
W
E
/
W
S
=
(
r
/
(
r
+
h
)
2
∗
x
)/
(
r
/
r
2
∗
x
)
=
(
6
3
7
0
0
0
0
2
×
x
)/
(
6
3
7
8
8
4
8
2
×
x
)
=
0
.
9
9
7
2
2
7
7
5
5
4
Now
1
−
W
E
/
W
E
=
1
−
0
.
9
9
7
2
2
7
7
5
5
4
=
2
.
8
×
1
0
−
3
SO.the answer is also
2
.
8
×
1
0
−
3
I used a calculator, got my answer as 0.0027 and I hate it now.
Log in to reply
You got 0 . 0 0 2 7 7 that means 0 . 0 0 2 8 .But if you give 0 . 0 0 2 7 7 as answer it will also be correct.
well done
very lenthy way
i round it to 3 x 10(sqr)-3 and it's wrong because of that :P
I posted the answer as 0.0027 by doing the same method.
We begin by finding the ratio of the gravitational field strength on Everest to Sea level: g s g e = r s 2 G M r e 2 G M = r e 2 r s 2
Using Newton's second law, F e = m a e
F s = m g s
so the ratio of the two forces due to gravity are, F s F e = g s g e = r e 2 r s 2 = 6 3 7 8 8 4 8 2 6 3 7 0 0 0 0 2 = 0 . 9 9 7
Finally, we subtract the ratio from one.
1 − F s F e = 1 − 0 . 9 9 7 = 0 . 0 0 2 7 7
Let x be your weight at sea level and r is the distance to the center of the earth
Your weight on the top of Everest will be (r / (r + height of Everest))^2 * x
Problem Loading...
Note Loading...
Set Loading...
Here,
G = 6 . 6 7 3 × 1 0 − 1 1 N m 2 k g − 2
M = 6 × 1 0 2 4 kg
R = 6 3 7 0 km = 6 3 7 0 0 0 0 m
h = 8 8 4 8 m
g E =( 6 . 6 7 3 × 1 0 − 1 1 N m 2 k g − 2 × 6 × 1 0 2 4 kg ) / ( 6 3 7 0 0 0 0 + 8 8 4 8 ) 2 m
So, g E = 9 . 8 3 9 8 3 6 1 8 m s − 2
Again, g S =( 6 . 6 7 3 × 1 0 − 1 1 N m 2 k g − 2 × 6 × 1 0 2 4 kg ) / ( 6 3 7 0 0 0 0 ) 2 m
So, g S = 9 . 8 6 7 1 9 0 4 4 6 m s − 2
Now,1- W E / W S
=1- ( m × g E )/ ( m × g S )
=1- ( 9 . 8 3 9 8 3 6 1 8 )/ ( 9 . 8 6 7 1 9 0 4 4 6 )
=1- 0 . 9 9 7 2 2 7 7 5 5 4
= 2 . 8 × 1 0 − 3
SO,The answer is 2 . 8 × 1 0 − 3